2000
DOI: 10.1021/la000297e
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Electrostatic Interaction Properties of Monolayers of Amphiphilic Molecules Derived from C60-Fullerenes:  A Film Balance, Neutron-, and Infrared Reflection Study

Abstract: Monolayers at the air/water interface of a new amphiphilic molecule derived from a C60-fullerene were studied at different lateral pressures by a combination of film balance techniques, neutron reflection (NR), and infrared reflection−absorption spectroscopy (IRRAS). The amphiphilic fullerene derivative (AF) consisted of a dendrimeric hydrophilic region, and 10 alkyl chains covalently attached to the fullerene cage formed the hydrophobic part. The AF monolayers could be compressed and expanded without signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 21 publications
1
42
0
1
Order By: Relevance
“…Recently, we introduced two examples, 1 [1,2] and 2, [3Ϫ5] of amphiphilic [5:1]-hexakisadducts of C 60 that involve an octahedral addition pattern. [6] The remarkably facile access to these stereochemically defined multiple adducts required control over the regioselectivity of the subsequent additions to the [6,6]-bonds in equatorial sites.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we introduced two examples, 1 [1,2] and 2, [3Ϫ5] of amphiphilic [5:1]-hexakisadducts of C 60 that involve an octahedral addition pattern. [6] The remarkably facile access to these stereochemically defined multiple adducts required control over the regioselectivity of the subsequent additions to the [6,6]-bonds in equatorial sites.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of C 60 materials science, studies deal with the self-organization of molecules having original ordered structures [1][2][3][4] and mainly thermotropic or lyotropic liquid-crystalline mesophases, micelles, membranes, or mono-and multilayered films [5][6][7][8][9][10]. However, the development of functional devices very often requires dedicated engineering of the molecules, that is, functionalization of the molecules for controlling their self-organization.…”
Section: Introductionmentioning
confidence: 99%
“…Both the SAM approach, achieved through junction moieties such as organosilane [16], organosulfur [17], or carboxylic acid [18], and the Langmuir technique allow control of the formation and the structure of the resulting film at a molecular level. In the latter field, working at the air-water interface, various [60]fullerene derivatives ranging from mono- [19][20][21][22][23][24][25], to bis- [26], up to hexa-adducts [27][28][29][30] have been studied in the past few years and showed encouraging results in terms of film quality and stability, roughness, reversibility, and transfer onto solid substrates. For example, Cardullo et al [31] or more recently Hirano et al [32] showed that fullerene mono-adducts bearing dendritic branches display good spreading characterisitics and reversible compression/ expansion behaviour has been described.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the C 60 units are buried in the middle of the dendrimer which provides an insulating layer around them, thus preventing the irreversible three-dimensional aggregation resulting from fullerene-fullerene interactions [39,40]. Finally, various studies performed very recently on [60]fullerene hexakisadducts [27][28][29][30] showed that hexa-addition on the carbon sphere provided not only an ideal structure to prevent aggregation phenomenon but also an optimised hydrophilic-hydrophobic balance for preparing well-ordered supramolecular assemblies at the air-water interface.…”
Section: Introductionmentioning
confidence: 99%